2023
DOI: 10.1038/s41598-023-34523-y
|View full text |Cite
|
Sign up to set email alerts
|

Flax fiber based semicarbazide biosorbent for removal of Cr(VI) and Alizarin Red S dye from wastewater

Abstract: In the present study, flax fiber based semicarbazide biosorbent was prepared in two successive steps. In the first step, flax fibers were oxidized using potassium periodate (KIO4) to yield diadehyde cellulose (DAC). Dialdehyde cellulose was, then, refluxed with semicarbazide.HCl to produce the semicarbazide functionalized dialdehyde cellulose (DAC@SC). The prepared DAC@SC biosorbent was characterized using Brunauer, Emmett and Teller (BET) and N2 adsorption isotherm, point of zero charge (pHPZC), elemental ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…9 ). This is consistent with other batch studies which also reported maximum Cr(VI) adsorption in acidic environments 37 , 66 , 67 and can be explained by considering the surface charges of the adsorbents and the Cr(VI) adsorbate species 68 . The surface charge of an adsorbent is determined by pHpzc where an adsorbent surface is neutral at pH = pHpzc, but develops a positive charge at pH < pHpzc and a negative charge at pH > pHpzc.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…9 ). This is consistent with other batch studies which also reported maximum Cr(VI) adsorption in acidic environments 37 , 66 , 67 and can be explained by considering the surface charges of the adsorbents and the Cr(VI) adsorbate species 68 . The surface charge of an adsorbent is determined by pHpzc where an adsorbent surface is neutral at pH = pHpzc, but develops a positive charge at pH < pHpzc and a negative charge at pH > pHpzc.…”
Section: Resultssupporting
confidence: 92%
“…Because of the strong protonation, the adsorbent surface becomes positively charged at low pH. The Cr(VI) adsorption was enhanced due to the electrostatic force between negatively charged HCrO 4 − and Cr 2 O 7 –2 and SO 3 − of (E110 and E122) and the positively charged adsorbent surface 37 . Thus, this, in turn, enhances the affinity of CS@CTAB material towards attracting positively charged metal ions and dye molecules depending on pH control, causing the improvement of Cr(VI), E110, and E122 adsorption as shown in the equations below (12) and (13), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation